2021
DOI: 10.18502/ijpa.v16i1.5509
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Effect of Chitosan Nanoparticles and Metronidazole in Treatment of Experimentally Giardiasis Infected Hamsters

Abstract: Background: The present study aimed to assess the therapeutic effect of chitosan nanoparticles and metronidazole against Giardia lamblia as well as evaluate the efficacy of loading metronidazole on chitosan nanoparticles. Methods: This study was carried out at medical Parasitology Department, Faculty of Medicine, Zagazig University and Theodor Bilharz Research institute (TBRI) from February 2019 to February 2020 on 45 hamsters. They were divided into 5 groups 9 hamsters each: Group A non-infected hamster… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…also showed that synthesized CNPs prepared by ionic crosslinking of chitosan solution at the dose of 5 ppm for 8 d significantly reduced the number of Giardia cysts in the stool and trophozoites in intestinal sections of rats with giardiasis[16].Recently, El-Gendy et al (2021) demonstrated that oral administration of CNPs at the dose of 50µg/hamster/day for 7 consecutive days alone and especially in combination with MTZ in Syrian hamsters infected with G. lamblia significantly reduced the cysts and trophozoites counts by 63.64-94.69%. They also reported significant healing of intestinal mucosa in the infected hamsters after treatment with MTZ+CsNPs[15].…”
mentioning
confidence: 88%
“…also showed that synthesized CNPs prepared by ionic crosslinking of chitosan solution at the dose of 5 ppm for 8 d significantly reduced the number of Giardia cysts in the stool and trophozoites in intestinal sections of rats with giardiasis[16].Recently, El-Gendy et al (2021) demonstrated that oral administration of CNPs at the dose of 50µg/hamster/day for 7 consecutive days alone and especially in combination with MTZ in Syrian hamsters infected with G. lamblia significantly reduced the cysts and trophozoites counts by 63.64-94.69%. They also reported significant healing of intestinal mucosa in the infected hamsters after treatment with MTZ+CsNPs[15].…”
mentioning
confidence: 88%
“…The association of chitosan nanoparticles with metronidazole also exhibited significant efficacy in treating experimental Giardiasis in hamsters [ 112 ].…”
Section: New Compoundsmentioning
confidence: 99%
“…Common anti-parasitic therapeutics, such as albendazole or nitazoxanide, are considered alternative therapeutic agents, but in some previous studies, these agents appeared to be mutagenic, with some carcinogenic activity [8]. Additionally, it is well known that some major medications have significant side effects [9], and other medications appear to have a pronounced potential for resistance [10].…”
Section: Introductionmentioning
confidence: 99%